Pharmaceutical Stability Testing to Support Global Markets - Huynh-Ba, Kim.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book is a proceedings of the AAPS Stability Workshop. This workshop provide an understanding of the regulatory perspective of Stability Testing and position the stability program for 21st century globally by: Learning regulatory initiatives on global stability submission. Stability testing in challenging storage environment such as ASEAN or Caribbean region. Exploring concept of Quality by Design as it applies to stability testing. Understanding stability challenges of biologics, generics, nutraceutical, and other new product technology. Setting specifications for Drug Substances as well as various type of drug products. Exploring concerns on changes of stability profiles such as repackaged products, split tablets. Discussing safety and toxicology concerns of emerging impurities. Understanding physical effects on product stability. Stability to support temperature excursion during shipping. Assessing impurities and degradation product in development. Leveraging stability data to expedite regulatory approval. Managing relationship with Contract Research Organizations.
Section I -- Stability Studies in a Global Environment -- Regulatory Perspectives on Product Stability -- Current International Harmonization Efforts -- Update on the WHO Stability Guideline -- Development of a Regional Guideline for the Eastern Mediterranean Region -- The Challenge of Diverse Climates: Adequate Stability Testing Conditions for India -- Requirements for South East Asian Markets -- The Role of USP Monographs in Stability Testing -- Regulatory Requirements for Stability Testing of Generics -- Stability Design for Consumer Healthcare Products -- Challenges of Drug/Devices Pharmaceutical Products -- Practical Challenges of Stability Testing of Nutraceutical Formulations -- Setting Tolerances for Instrument Qualification USP Chapter -- Technical Concepts for Stability Program -- The Concept of Quality-by-Design -- Forced Degradation and Its Relation to Real Time Drug Product Stability -- Low Level Impurities in Drug Substances and Drug Products and the Analytical Challenges in Identification and Quantitation -- Stability of Repackaged Products -- Packaging-Induced Interactions and Degradation -- An Overview of Physical Stability of Pharmaceuticals -- Stability of Split Tablets -- Temperature Monitoring During Shipment and Storage -- Introducing a Science-Based Quality by Design Concept to Analytical Methods Development -- Stability Data and Operational Practices -- Optimizing Stability Data Package to Facilitate NDA/MAA Approval -- Maximize Data for Post Approval Changes -- Use of Statistics to Establish a Stability Trend: Matrixing -- Setting Specifications for Drug Substances -- Setting Specifications for Drug Products -- Highlights of Investigating Out-of-Specifications Test Results -- Strategies for Ensuring Regulatory and cGMP Compliance of Outsourced Stability Programs -- Building and Developing of Relationships with Third Party Laboratories -- Outsourcing Stability Testing: A Tool for Resource and Risk Management.
Keywords: Medicine; Toxicology; Biomedicine; Pharmacology/Toxicology.